Analisis Pola Asuh Anak Usia Dini dalam Menerapkan Pendidikan Agama Islam di KBIT Ulil Albab Kebumen - farokhah, Abdah jalalatul; Wi Hargina, Devi Yaniar (IAINU Kebumen, 2026)
The research objectives were: (1) To find out how the parenting style was carried out by the teacher in learning Islamic Religious Education at KBIT Ulil Albab Kebumen. (2) Describe the inhibiting and supporting factors of early childhood parenting carried out by teachers in learning Islamic Religious Education at KBIT Ulil Albab Kebumen. This research uses descriptive qualitative method. Informants in this study were school principals, formal teachers, tpq teachers and guardians of students. This research data collection technique using interviews, observation and documentation. The data analysis technique used is (1) data reduction, (2) data presentation, (3) conclusion. Based on the research and discussion above, KBIT Ulil Albab Kebumen only has two forms of parenting that are applied, namely authoritarian parenting and democratic parenting. The supporting and inhibiting factors in this implementation are, Supporting Factors: (1) Delay in the arrival of children; (2) Children's concentration; (3) The child's psychological condition. While the Inhibiting Factors are: (1) Delay in the arrival of children; (2) Children's concentration; (3) The child's psychological condition.